Development of turbulence for high pressure natural gas transmission pipelines - Yeo, Jie Neng (2016)
In Singapore, mostly of the electricity is being generated by using natural gas as fuel. In the near future Singapore will be expecting to use more on natural gas to generate electricity. Currently, Singapore’s natural gas is being imported from Malaysia and Indonesia via four offshore pipelines. The author designed and fabricated two different cases to simulate the air flow through the pipe; they are pipe with a hole and with a dent. This help to examine the flow phenomenon within the gas pipeline to understand how to detect turbulence in the defected pipeline. The turbulence of the pipeline is dependable on the Reynolds number and Mach number of the air in the pipe. There will be two different case of simulation being carried out in this project. Firstly is the 2D simulation with dent to find out the effect of external interference introduced defect and then 3D simulation on the effect of leakage on the pipeline. In these simulations is to create a reference values for leakage detection where it analysis the differences on temperature distribution and strain distribution on the pipeline.